Isobaric Tags for Relative and Absolute Quantitation (iTRAQ)-Based Proteomic Analysis of Hugan Qingzhi and Its Protective Properties against Free Fatty Acid-Induced L02 Hepatocyte Injury - Xia, Fan; Yao, Xiaorui; Tang, Waijiao; Xiao, Chunxin; Yang, Miaoting; Zhou, Benjie (Frontiers in Pharmacology, 2017)
In previous research, Hugan Qingzhi, a traditional Chinese medicine, was shown to have protective effects against hepatic steatosis. However, its activity against nonalcoholic fatty liver disease (NAFLD) and the mechanisms by which it exerts its effects remain unknown. In the present study, the effects of Hugan Qingzhi on free fatty acid-induced L02 cells were examined. The techniques of iTRAQ labeling, together with strong cation exchange-non-liquid chromatography–tandem mass spectrometry (SCX-non-LC-MS/MS) analysis and serum pharmacology, were used to evaluate the effects of Hugan Qingzhi-medicated serum on free fatty acid-induced L02 hepatocyte injury. Results identified 355 differentially expressed proteins following free fatty acid treatment, compared with a control group; 359 altered proteins in the Hugan Qingzhi high dose + free fatty acid treatment group, compared with the free fatty acid treatment group; and 365 altered proteins in the Hugan Qingzhi high dose + free fatty acid treatment group, compared with the control group. Based on the Kyoto Encyclopedia of Gene and Genomes pathway enrichment analysis, it is concluded that several pathways including those of microbial metabolism in diverse environments, fatty acid metabolism, peroxisome proliferator activated receptor signaling, and mitogen-activated protein kinase signaling are closely associated with the effects of Hugan Qingzhi-medicated serum in free fatty acid-induced L02 hepatocyte injury. Furthermore, several differentially expressed proteins, including heat shock protein 27 (HSP27), acetyl-CoA acetyltransferase 1, calnexin, and integrin-linked kinase, were validated by western blotting. A target-specific HSP27 siRNA was used to investigate further the function of HSP27, and it was found that HSP27 might have a key role in the observable effects of Hugan Qingzhi-medicated serum in free fatty acid-induced L02 hepatocyte injury. The results not only confirmed that Hugan Qingzhi exhibits a significant protective effect in free fatty acid-induced L02 hepatocyte injury, but also suggest insights into the mechanism of such protective effects.